2022
DOI: 10.3390/foods11182744
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 18 Free Amino Acids in Honeybee and Bumblebee Honey from Eastern and Northern Europe and Central Asia Using HPLC-ESI-TQ-MS/MS Approach Bypassing Derivatization Step

Abstract: The profile of amino acids and mono- and disaccharides in conventional polyfloral honey originated from Latvia and Tajikistan and less found in nature bumblebee honey from Russia was investigated. The analysis of free amino acids (FAAs) accomplished by multiple reaction monitoring (MRM) using triple quadrupole mass selective detection (HPLC-ESI-TQ-MS/MS) revealed the presence of 17 FAAs. The concentration of FAAs varied in the range of 0.02–44.41 mg 100 g−1 FW. Proline was the main representative of FAAs, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Among behavioral similarities, some floral volatiles were shown to attract both insects [ 55 ]. A comparative study of honeybee and bumblebee honeys from different geographical and botanical origins reported a similar qualitative composition of free AAs between the two types of honeys, although the quantitative composition was different [ 56 ]. Another comparative study reported recently that honeybees and bumblebees both avoid foraging nutritionally poor (e.g., having low protein and high lipid content) and highly toxic pollen, compared to other insects [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among behavioral similarities, some floral volatiles were shown to attract both insects [ 55 ]. A comparative study of honeybee and bumblebee honeys from different geographical and botanical origins reported a similar qualitative composition of free AAs between the two types of honeys, although the quantitative composition was different [ 56 ]. Another comparative study reported recently that honeybees and bumblebees both avoid foraging nutritionally poor (e.g., having low protein and high lipid content) and highly toxic pollen, compared to other insects [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…A significant decrease in proline concentration in honey was reported when honeybee was fed with sucrose rather than pollens (Nisbet et al, 2018). The prevalence and the pollen origin make proline an important criterion for detecting honey adulteration (Dimins et al, 2022). Buckwheat honey contained the highest total free amino acid content, and total branched-chain amino acids (BCAA), including leucine, isoleucine and valine.…”
Section: Total Protein Content and Characterization Of Amino Acids Pr...mentioning
confidence: 99%
“…Except for the predominant proline which originates from the hypopharyngeal glands in the worker honeybee (Davies, 1978), some other free amino acids were identified as botanical markers. For examples, leucine, isoleucine, and tyrosine are major amino acids in buckwheat honey (Dimins et al, 2022), and asparagine is enriched in ilex honey (Paramás et al, 2006). A non-proteinogenic amino acid, γ-aminobutyric acid, was unique to chestnut-tree honey (Paramás et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The composition of amino acids in honey is dependent on the pollen species from where the nectar originates, therefore, it can serve as an index for botanical differentiation [56,254]. Proline, originated from the salivary secretion of bees acting on honey collection and maturation, has been found in higher amounts than the other amino acids in honeys, as the major contributor with 50-85% of the total amino acids [208,255,256], while in some studies, phenylalanine has been reported to be the predominant one [253,257]. In general, honeydew contains higher amounts of amino acids than floral honeys [203], and can be differentiated from raw floral honey by amino acids composition in all amino acids except for phenylalanine, tyrosine, and proline [255].…”
Section: Amino Acids/proteinsmentioning
confidence: 99%